Persepsi nasabah tentang kepuasan dan loyalitas terhadap kualitas layanan di BMT Sukosari - Kholiza, Siti Nur; Hidayatullah, Mohammad Alief (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
BMT is one form of microfinance institution in Indonesia, this institution is present to develop productive businesses of small and medium economic actors and improve the economic quality of the community in the context of poverty alleviation efforts and support the financing of economic activities, this study aims to determine customer perceptions of the quality of Islamic banking services, investigate the perceptions of Islamic bank users in Sukosari and the reasons they are interested or not Using Islamic banking whether because of sharia considerations or quality. The data collection technique was carried out by distributing questionnaires to 60 BMT Sukosari customers. The sampling technique uses purposive sampling. This research is a quantitative research with multiple linear regression data analysis tools with the help of SPSS software version 15.0. The results of this study show that there is a positive and significant influence of customer satisfaction and customer loyalty simultaneously on customer perceptions regarding the quality of service KSPSS BMT Sukosari Branch. Based on the results of simultaneous tests obtained fcalculate values of 46.349 > ftable 3.16 with significant results less than 0.005, which means proving Ha3 is accepted and HO3 is rejected. The results of the coefficient of determination (R2) test with an Adjusted R Square (R2) value of 0.606 or (60.6%) mean that the variables of customer satisfaction and customer loyalty have a significant effect on the perception of service quality of KSPSS BMT Sukosari Branch